Practice tests for use with Psychology : - Lahey, Benjamin B. (McGraw-Hill, 2009)
A contemporary take on a time tested classic. Students will master the central concepts of psychology with the new 10th edition of Psychology from Benjamin Lahey. A new chapter on the Interplay of Nature and Nurture highlights the 10th edition’s new organization and streamlined content . Lahey weaves scholarship based on empirical research throughout the text, ensuring an accurate portrait of contemporary psychology. The text’s student-friendly writing, new chapter openers, and fresh applications make the material more relevant to students than ever before, and the proven learning system ensures that all students will grasp the concepts presented in the book. Lahey’s hallmark emphasis on diversity and culture remains integrated throughout the text, making this the text for a well rounded introduction to all areas of psychology.